Hubungan Kualitas Tidur Dengan Kadar Glukosa Darah Sewaktu Pada Pasien Diabetes Melitus Tipe 2 - Muhamad Sasiar Tajiwalar; I Gede Angga Adnyana; Made Rika Anastasia Pratiwi (Journal of Pharmaceutical and Health Research, 2023)
Background: Disturbances in the quantity and quality of sleep will trigger impaired glucose tolerance and reduce insulin sensitivity, affecting blood glucose levels. This situation can worsen the condition of people with type 2 Diabetes Mellitus. Objective: To determine the relationship between sleep quality and blood glucose levels in patients with type 2 diabetes mellitus at the Praya Public Health Center. Research method: Analytical research uses an observational approach with a cross sectional research design. The sample used was type 2 Diabetes Mellitus patients totaling 181 people taken by purposive sampling technique by measuring blood sugar levels while using the glucotest and providing a Pittsburgh Sleep Quality Index (PSQI) sleep quality questionnaire in data collection. Data were analyzed using spearman's rho. Result: The results of the study of respondents based on blood glucose levels at <200 (89 people) consisted of good sleep quality 96.6% and bad 3.4% while >200 (92 people) with good sleep quality 17.4% and bad 82.6 %. This shows that respondents experience hyperglycemia if the quality of sleep is poor. The analysis using Spearman's rho showed a significant relationship between sleep quality and blood glucose levels (p-value = 0.01) in type 2 Diabetes Mellitus patients at the Praya Health Center. Conclusion: There is a relationship between sleep quality and blood glucose levels in patients with type 2 diabetes mellitus at the Praya Public Health Center.